“I’m never tasting surrender again”. - Maguire, Patrick (New Statesman, 2019)
The author presents comments from British member of Parliament Steve Baker on the British withdrawal from the European Union. He mentions Baker's stance on voting against Prime Minister Theresa May's proposals for the withdrawal, his views on the possible collapse of the Conservative Party, and his reluctance to compromise.